Evaluasi User Interface Pada Aplikasi Just Meme Menggunakan Heuristic Evaluation Method - Ryu Wilsal, Ryu; Rahman, Syaiful; Arianti, Arianti (KHARISMA Tech, 2024)
Just Meme is a mobile application used for expressing people's feelings by creating stickers, GIFs, and funny videos. The aim of this research is to evaluate the user interface of the Just Meme application using the Heuristic Evaluation Method. Prior to this study, the researcher conducted an evaluation with 20 users of the Just Meme application, resulting in a plethora of user comments. Consequently, the researcher decided to assess the quality of the user interface in the Just Meme application with the goal of ensuring user satisfaction with the new feature displays and attracting more users to use this application. This was accomplished by distributing questionnaires to individuals considered experts in the field. The research findings, based on the ten principles of Heuristic Evaluation, revealed two principles with significantly higher scores than the others. Firstly, "recognition rather than recall" received a total score of 1.444 (cosmetic problem), indicating no need for improvement as it does not affect the user. Secondly, "Help and Documentation" scored similarly, with a total of 1.333 (cosmetic problem), suggesting that no significant improvements are required, and it does not impact the user